PENINGKATAN KESADARAN MASYARAKAT TENTANG BAHAYA MINYAK JELANTAH MELALUI KEGIATAN SOSIALISASI DI DESA DAYUREJO, PRIGEN, PASURUAN - Utami, Desy Cahyaning; Palupi, Hapsari Titi; Arifin, Ahmad Zainul (FKIP Universitas Wisnuwardhana, 2025)
Waste cooking oil poses environmental and health risks if improperly managed. This community service study aimed to enhance the knowledge and skills of residents in Dayurejo Village, Prigen, in safe and environmentally friendly waste cooking oil management through a socialization program involving the Pemda 9 youth group. Methods included interactive lectures, practical demonstrations of converting waste oil into useful products, and discussion sessions. Pre- and post-activity questionnaires assessed changes in participants’ knowledge and skills. Results showed significant improvements: awareness of waste oil hazards increased from 40% to 90%, knowledge of safe handling from 20% to 85%, and ability to identify environmental impacts from 35% to 88%. Interactive and hands-on approaches effectively promoted awareness and active participation. Regular implementation of similar programs is recommended to support a cleaner, healthier, and more productive environment.